Data Storytelling - Quansah, Ebenezer Nana Kojo (Univerzita Pardubice, 2024)
The thesis titled "Data Storytelling" by Ebenezer Quansah aims to explore the concept of data storytelling and it’s contrast with common presentation practices. The work will focus on the use of appropriate visualisation tools and the principles of data storytelling. It will also delve into the differences between data-driven presentations and data storytelling, assessing the benefits and drawbacks of each approach. The thesis will emphasise the importance of effective visuals and story structure in data storytelling, as well as the use of annotations to highlight relationships and trends in the data.
Keywords: data storytelling; visualization; story structure; data